Promosi dan Customer Relationship Management Terhadap Kepuasan Pengguna Shopee Pay Pasca Pandemi - Irfan Ardiansyah*; Desti Dirnaeni; Christera Kuswahyu Indira (Universitas Syiah Kuala, 2023)
This study aims to determine the effect of promotions and Customer Relationship Management (CRM) on post-pandemic Shopee pay user satisfaction. The population in this study are people who use the Shopee Pay e-wallet and live in Jabodetabek, because the population size is unknown, the unknown population formula from Rao Purba (1996) is used with an error rate of 5%, the result is 384 respondents to be the sample of this study. Data collection techniques by distributing questionnaires and the methods used in this study are validity, reliability, classical assumption test, multiple linear regression partial test, simultaneous test and determination test. Based on the results obtained, it can be seen that partially and simultaneously promotions and customer relationship management have an effect on post-pandemic post-pandemic post-pandemic Shopee Pay user satisfaction.